APPROPRIATE BASE STIFFNESS OF SMART BASE ISOLATION SYSTEM (Malaysian Journal of Civil Engineering, 2018)
In this paper, the effect of base stiffness on the performance of hybrid control system of base isolation system and magnetorheological (MR) damper has been studied and its appropriate base stiffness has been determined. Many researches have been proposed that in the structure controlled by the single base isolation system without MR damper, the base stiffness should be designed such that the fundamental period of isolated structure is almost triple the fundamental period of fixed-base structure. To determine the appropriate base stiffness of hybrid control system, different values have been considered as base stiffness and MR damper has been also employed in two cases of passive form that voltage and dynamical behaviour of MR damper is constant (hybrid base isolation) and semi-active form that MR damper voltage is applied by H2/linear quadratic Gaussian (LQG) and clipped-optimal control algorithms (smart base isolation). For numerical simulation, a three-story shear frame has been subjected to El Centro, Northridge and Tabas earthquakes. Results show that in the structure controlled by the single base isolation system, the peak responses of structure strongly depend on the base stiffness while the sensitivity of peak responses to the base stiffness is lower when the structure is controlled by hybrid base isolation system. According to results, it can be concluded that the peak base drift of hybrid base isolation system reduces with the increase of the base stiffness while this reduction trend is less considerable in the stiffness that are more than the proposed stiffness for the single base isolation system. Hence the proposed stiffness for single base isolation system is the appropriate stiffness for hybrid base isolation system, too. Results also show that under earthquakes considered in this paper, the smart base isolation system is mostly more effective than hybrid base isolation system in mitigating and controlling both root mean square and maximum of structure responses such as base drift, inter-story drift and acceleration.